Implementasi Dan Analisis Vpn Untuk Keamanan Komunikasi Voip Pada Jaringan Cloud - Bima Sanjaya; Rendy Munadi; Leanna Vidya Novita (eProceedings of Engineering, 2015)
Abstract— Security becomes a very vital part in the development of computer networks, especially in VoIP Communication and Cloud Network. In this final project is implemented Infrastructure As A Service on Cloud Computing system to running a VoIP server and OpenVPN VPN systems, SSTP, and IKEv2 / IPSec as supporting VoIP communications security and Cloud systems. Security aspects will be analyzed VoIP server from DDoS attacks and VoIP communication with sniffing method will then try backing playback RTP packet sent. Included also will be analyzed aspects of performance VoIP communications itself. Scenarios will be done with and without the use of VPN systems. From the test results it can be concluded that the addition of VPN on the server Asterisk-based Cloud Computing will add aspects of integrity, confidentiality, and authentication on VoIP communications, while the results of measurements of quality of VoIP communications obtained lowest quality of QoS is delayt 44 ms, jitter 0.99 ms, packet loss 0% and MOS 4.01. The performance of various VPN systems almost the same and VPN solutions can not only secure communications of VoIP itself but also useful for securing VoIP servers from DoS attacks. Keywords—VoIP; Security; DDoS; VPN; QoS